1978
DOI: 10.1007/bf00036503
|View full text |Cite
|
Sign up to set email alerts
|

The Freshwater co-occurrence of Eurytemora Affinis (Copepoda: Calanoida) and Manayunkia Speciosa (Annelida: Polychaeta): Possible relicts of a marine incursion

Abstract: The copepod Eurytemora affinis (Poppe, 1880) and the polychaete Manayunkia speciosa Leidy, 1858 have been found in similar habitats within the Ottawa River . As both species show strong marine affinities and co-occurrence is not restricted to the Ottawa River, but rather is the pattern for North America, present evidence supports the theory that these animals may be relict forms resulting from the most recent marine incursion .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Burkill and Kendall's (1982) in situ experiments suggested that E. affinis is capable of reproducing at 30%0 S, confirming laboratory experiments by Katona (1970), who recorded that this copepod reproduced at 33%0 S as equally successfully as at 5 or 20%0 S, and with no significant difference in generation times. In contrast, freshwater records for E. affinis are by no means infrequent (Croskery 1978). Heckman (1986) found breeding populations of E. affinis in freshwater areas of the Elbe estuary as well as in brackish-water areas.…”
Section: Discussionmentioning
confidence: 84%
“…Burkill and Kendall's (1982) in situ experiments suggested that E. affinis is capable of reproducing at 30%0 S, confirming laboratory experiments by Katona (1970), who recorded that this copepod reproduced at 33%0 S as equally successfully as at 5 or 20%0 S, and with no significant difference in generation times. In contrast, freshwater records for E. affinis are by no means infrequent (Croskery 1978). Heckman (1986) found breeding populations of E. affinis in freshwater areas of the Elbe estuary as well as in brackish-water areas.…”
Section: Discussionmentioning
confidence: 84%
“…Their ancestors may have been stranded during past, relatively recent, climatic (e.g., glaciations and marine transgressions) or eustatic (tectonic uplift) events. A freshwater relict is indicated when there is co-occurrence with unrelated taxa and both show close affinities with marine species in the region (e.g., Croskery, 1978; Schmidt Table 2 Numbers of polychaete species and genera (in parentheses) for each major habitat, arranged alphabetically by family Family Lake/River Estuary/Lagoon Inland Sea Oases/Springs Hyporheic zone Subterranean water Phytotelmata (Croskery, 1978;Hutchings et al, 1981;Schmidt & Westheide, 1999). Freshwater species of a third category are the temporary (either space or time) inhabitants of waters with fluctuating salinity such as estuaries and coastal lagoons, including many Nereididae, Spionidae, and the serpulids, Ficopomatus species.…”
Section: Phylogeny and Zoogeographymentioning
confidence: 99%
“…The species was then recorded in new localities, such as Lake St. Clair (Ontario, Michigan), St. Marys River (Ontario, Michigan), the Sevenmile Canal (Oregon), two lakes in northern Alaska, the Ottawa River, Cayuga Lake (New York), Simmon's Bayou (Mississippi), besides being collected again in Lake Erie (Hiltunen 1965;Britt 1965;Hazel 1966;Holmquist 1967;Mackie and Qadri 1971;Spencer 1976;Croskery 1978;Brehm 1978). Its distribution by that time covered the east-and west-coast river systems of North America, the Great Lakes region, and the coast of the Gulf of Mexico.…”
Section: Introductionmentioning
confidence: 99%